Dyett, David (London, 2011)
2011 "Dyett, David", 2011, HistoryTalk He did a seven- year apprenticeship as a machine minder. After National Service he went to work as a printer for 12 years, then worked casually for about 16 years printing a huge range of different items like business cards and cheques. Decribes 'hot lead' printing and linotype printing for newspapers. He then moved to Barclay & Fry's followed by Daily Mirror/ Times/ News International for nearly 6 years until the introduction of laser printing. Describes working on at the Daily Mirror in Doughty Street during the Maxwell era and hours of work and pay rates. His last job was at Crown Cork Ltd in Southall and describes the workplace and hours of work